Use of the stages of concern questionnaire in a national top-down reform effort. (April 2019) - Fischer, Christian; McCoy, Ayana; Foster, Brandon; Eisenkraft, Arthur; Lawrenz, Frances
Abstract: The Stages of Concern (SoC) dimension of the Concerns-Based Adoption Model is a developmental framework to measure teachers' concerns during curricular changes. The SoC has rarely been used in a large-scale, top-down science curriculum change such as the Advanced Placement Science redesign. Our quantitative and qualitative analyses showed that the SoC may not adequately measure teachers' concerns when faced with such a large change. The SoC measurement characteristics were shown to have some weaknesses and the proposed developmental tendency toward teachers having higher level concerns as the reform progressed was not found in the data collected about this reform. Highlights: Stages of Concern instrument had weak measurement characteristics. Teachers showed concerns at all Stages of Concern. Limited documentable upward trend over time in teachers' Stages of Concern. The nature of the reform could have affected the teachers' Stages of Concern.